Optimizing Apartment Management through Extreme Programming-based CRM Application - Denny Jean Cross Sihombing (SEAN Institute, 2023)
This research aims to develop a Customer Relationship Management (CRM) application specifically for the apartment industry using the Extreme Programming (XP) approach. This approach involves identifying customer needs, creating user stories, and prioritization to ensure application responsiveness. The resulting system has a microservices design, a friendly user interface, and a high level of security. The implementation of quality code involved pair programming and automated testing. The testing process involves User Acceptance Testing (UAT) with the participation of apartment residents to obtain feedback that is applied to improvements. A small and frequent release approach ensures optimal quality and functionality. User involvement through UAT and retrospective sessions ensures the solution matches expectations, providing a positive user experience. By applying XP principles, this research successfully created a responsive, adaptive, and user-orientated CRM application to meet the complex needs of the apartment industry.